L'importance d'être et de paraître (Don) Sébastien - Santos, Maria do Rosário Girão (2017)
At the crossroads between “saudade”, the feeling of longing, and the coming of the Fifth Empire, King Sebastian establishes himself as the Portuguese literary myth, characterised by an incessant emotional flow inherent to the mythemes The Desired One/The Concealed One and crystalised in a vast iconic-verbal production, among which Almeida Faria’s The Conqueror (1990) and Agustina Bessa-Luís’s The Monastery (1980) stand out. On the one hand, we have the parodic desacralisation of myth; on the other, the reconstruction of the personality of the Monk-King as the son of tears, the captive of fear and the victim of an insane dream